Penerapan Prudentialprinciples Dalam Pemberian Modal Usaha Kecil Bank Syariah Mandiri KCP Aksara - Evi Febriani Rambe (FEB Universitas Maritim Semarang, 2023)
This research aims to describe the application of the precautionary principle in dealing with bad credit and to determine the assessment in providing financing to PT. BSM Kcp Script. This type of research is descriptive qualitative, data collection techniques use interviews and documentation, data analysis uses qualitative data analysis techniques using inductive thinking, and this research data uses primary data sources obtained from supporting sources, namely books, the internet and literature. other. PT. BSM Kcp Aksara has applied the precautionary principle in bad credit using the 5C principle analysis, which includes Character, Capacity, Capital, Condition and Colliteral as well as producers that customers must go through in submitting financing applications, providing financing, paying financing installments and obstacles to bad credit. . The results of this research, PT. BSM Kcp Aksara in implementing the principle of prudence in the financing that has been carried out is not good enough, BSM provides financing by emphasizing the 5C principle which includes Character, Capacity, Capital, Condition and Collateral. The important thing in providing financing to customers is Collateral (Guarantee). Judging from the results of customer data, the 5C principle has not been able to completely prevent bad credit due to the Account Office (AO) being less careful in analyzing financing. However, BSM's consistency in handling problematic financing customers has been carried out according to producers by collecting them periodically and providing warning letters I, II and III in stages.